2016
DOI: 10.3329/dujbs.v25i2.46341
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of fungicides and plant extracts on the growth of Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. and Sclerotium rolfsii Sacc. the causal organisms of anthracnose and soft rot of jute

Abstract: not available Dhaka Univ. J. Biol. Sci. 25(2): 195-199, 2016 (July)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Imtiaj et al (2005) found that plant extracts such as C. longa was also most effective against C. gloeosporioides the causal agents of anthracnose of mango. Hosen et al (2016) also observed inhibition of the growth of the jute pathogen C. gloeosporioides with C. limon, D. metel and A. indica at 20% concentration. Plant parts and their constituents of some higher plants have already been reported to be of successful nature of fungitoxicants, lesser phytotoxicity, systemicity, easily biodegradability and favourable effects of the growth of the host (Fawcett andSpencer 1970, Pandey et al1983).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Imtiaj et al (2005) found that plant extracts such as C. longa was also most effective against C. gloeosporioides the causal agents of anthracnose of mango. Hosen et al (2016) also observed inhibition of the growth of the jute pathogen C. gloeosporioides with C. limon, D. metel and A. indica at 20% concentration. Plant parts and their constituents of some higher plants have already been reported to be of successful nature of fungitoxicants, lesser phytotoxicity, systemicity, easily biodegradability and favourable effects of the growth of the host (Fawcett andSpencer 1970, Pandey et al1983).…”
Section: Resultsmentioning
confidence: 73%
“…Plant constituents have been reported to be successful fungitoxicants because of low phytotoxicity, easy biodegradability and favorable effects for the growth of the host (Fawcett and Spencer 1970, Panday et al 1983and Nene and Thapliyal 1993. Extracts obtained from many plants have recently studied for their antifungal activities (Monoharachary and Reddy 1978, Miah et al 1990, Hosen et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant constituents have been reported to be successful fungitoxicants because of low phytotoxicity, systemicity, easy biodegradability and favorable effects for the growth of the host (Fawcett andSpencer 1970 andPanday et al 1983). Extracts obtained from many plants have recently been studied for their antifungal activities (Monoharachary and Reddy 1978, Ahmed and Sultan 1984, Miah et al 1990, Hosen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many research workers evaluated the efficacy of fungicides against Colletotrichum spp. under laboratory and field conditions (Hosen et al 2016, Mamun et al 2016. Recently, plant extracts play an important role in the preservation of foodstuffs against fungi and have potential to replace synthetic fungicides (Tripathi and Shukla 2007).…”
mentioning
confidence: 99%